GE_GERICHTE P/23067/2025 vom 30. Oktober 2025 - GE Cour de justice (2025)
DÉTENTION PROVISOIRE;RISQUE DE FUITE;MESURE DE SUBSTITUTION À LA DÉTENTION;PROPORTIONNALITÉ | CPP.221.al1.leta; CPP.237; CPP.197